Polymer, preparation method thereof, positive pole piece, secondary battery and electric device
By using a polymer containing a phosphate group or a phosphite group as a dispersant, the problems of low solid content of the slurry and long drying time in the secondary battery are solved, and the effect of improving the solid content of the slurry and the flexibility of the slurry sheet is achieved.
Patent Information
- Application Number
- CN202311098921.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-29
AI Technical Summary
In existing secondary batteries, high solvent content slurry needs to be dried for a long time, resulting in low production efficiency and high cost. How to ensure uniform dispersion while improving the solid content of the slurry is a technical challenge.
A polymer containing a phosphate or phosphite group is used as a dispersant. The polymer contains a polyether segment and a polyester segment, which can effectively increase the maximum solid content of the positive electrode slurry and improve the electrode through anchoring action. Flexibility of the sheet.
It is achieved to increase the maximum solid content of the slurry, shorten the filtration time, improve the production efficiency and quality of the slurry, and at the same time improve the flexibility of the slurry and reduce the manufacturing cost.
Smart Images

Figure CN119431767A_ABST
Abstract
Description
[0001] Cross-references
[0002] This application refers to Chinese Patent Application No. 202310961340.X filed on August 1, 2023, entitled “Polymer, Preparation Method thereof, Positive Electrode Plate, Secondary Battery, and Electrical Device,” which is incorporated herein by reference in its entirety. Technical Field
[0003] The present application relates to the technical field of secondary batteries, and in particular to a polymer, a preparation method thereof, a positive electrode sheet, a secondary battery, and an electrical device. Background Art
[0004] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0005] The pole pieces in secondary batteries are often prepared by coating a slurry containing active materials on a current collector and then drying it. Increasing the solvent content in the slurry and reducing the solid content of the slurry are effective means to optimize the uniformity of slurry dispersion and improve the quality of slurry coating. However, slurries with high solvent content require long drying times and high manufacturing costs. How to ensure the uniformity of slurry dispersion while increasing the solid content of the slurry, and thereby effectively increase the maximum solid content of the slurry, is a technical problem that urgently needs to be solved in this field. Summary of the invention
[0006] The present application is made in view of the above-mentioned problems, and an object of the present application is to provide a dispersant capable of increasing the maximum solid content of a slurry.
[0007] The first aspect of the present application provides a polymer, wherein the polymer comprises a structure shown in Formula I,
[0008]
[0009] Wherein X comprises a phosphate group or a phosphite group, R 1 , R 3 Each independently contains at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and R 1 , R 3 At least one of them comprises a polyether segment or a polyester segment; 2 Contains organic segments.
[0010] The polymer can effectively increase the maximum solid content of the positive electrode slurry, shorten the filtration time, improve the production efficiency and quality of the electrode, and improve the flexibility of the electrode.
[0011] In any embodiment, R 2The organic chain segment contains at least one of an amide group, an amino group, and an aromatic group.
[0012] The nitrogen-containing groups or aromatic groups in the polymer help to improve the anchoring effect between the polymer and the positive electrode active material, making the polymer particularly suitable for carbon-coated positive electrode active materials, further improving the versatility of the polymer as a dispersant, and more effectively exerting the dispersing effect of the polymer by increasing the anchoring sites of the dispersant, thereby further increasing the maximum solid content of the slurry, improving the quality of electrode molding, and reducing costs and increasing efficiency.
[0013] In any embodiment, R 2 The organic chain also includes C 2-12 Hydrocarbon.
[0014] The polymer contains C 2-12 The hydrocarbon group helps to further improve the anchoring effect between the polymer and the carbon-modified positive electrode active material. The hydrocarbon group can effectively anchor to the carbon on the positive electrode active material, increasing the dispersion of the anchoring sites of the polymer on the positive electrode active material, thereby further improving the application range of the polymer dispersant, increasing the maximum solid content of the slurry, optimizing the quality of electrode molding, and reducing costs and increasing efficiency.
[0015] In any embodiment, R 2 Containing the structure shown in formula II
[0016]
[0017] Among them, R 4 With R 5 Random copolymerization, R 4 Including C 2-12 Alkylidene, C 3-13 At least one of the amide groups, R 5 include
[0018] At least one of;
[0019] Wherein, q1, q2, q3, q4 each independently include any integer between 0 and 4, R 6 a , R 6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
[0020] The organic chain segments of the above structure can more effectively play an anchoring role through copolymerization of nitrogen-containing groups and hydrocarbon groups, enhance the dispersion effect of the polymer, and effectively increase the solid content of the slurry.
[0021] In any embodiment, R 2 Containing the structure shown in formula III
[0022]
[0023] Among them, R 6 Including C 2-12 Alkylene, R 7 include At least one of; wherein, q5 and q6 each independently include any integer between 0-4, 1≤n≤6.
[0024] The organic chain segments of the above structure can more effectively play an anchoring role through the alternating copolymerization of nitrogen-containing groups and hydrocarbon groups, enhance the dispersion effect of the polymer, and effectively increase the solid content of the slurry.
[0025] In any embodiment, R 2 The terminal groups contain -C(O)-NH 2 、-CH 2 -NH 2 At least one of.
[0026] The terminal group contains -C(O)-NH 2 、-CH 2 -NH 2 The polymer can play a more effective dispersing role, increase the maximum solid content of the slurry, and thus improve the molding quality and efficiency of the pole piece.
[0027] In any embodiment, R 1 , R 3 At least one of them comprises a polyether segment, optionally, R 1 and R 3 All of them include polyether segments.
[0028] In any embodiment, R 1 , R 3 At least one of the polyether segments comprises a polyether segment of formula IV
[0029]
[0030] EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, 4≤m1≤50, 4≤n1≤50.
[0031] The polyether segment with the above structure has suitable steric hindrance and low glass transition temperature, which can more effectively reduce the order and glass transition temperature of the binder crystallization in the positive electrode slurry, thereby reducing the crystallinity of the binder and improving the flexibility of the electrode. Through the effects of dispersion and flexibility, the uniformity and flexibility of the electrode are improved, thereby improving the safety performance and ultimate compaction density of the battery, so that the positive electrode active material loading of the battery can be increased, which helps to further improve the energy density of the battery.
[0032] In any embodiment, the terminal groups of the polyether segments include aromatic groups.
[0033] The aromatic group has excellent compatibility with the carbon layer on the surface of the positive electrode active material, which helps to further improve the anchoring effect between the polymer and the carbon-modified positive electrode active material. The aromatic group and the carbon on the positive electrode active material can be effectively anchored to increase the dispersion of the anchoring sites of the polymer on the positive electrode active material, thereby further improving the application range of the polymer dispersant, increasing the maximum solid content of the slurry, optimizing the quality of electrode molding, and reducing costs and increasing efficiency.
[0034] In any embodiment, X comprises a phosphate group.
[0035] Phosphate polymers can more effectively increase the solid content of the slurry, shorten the filtration time, and improve the flexibility of the electrode; and phosphate polymers have better stability, and can effectively improve the battery's cycle capacity retention rate on the basis of improving the slurry's dispersibility.
[0036] In any embodiment, the polymer comprises at least one of the polymers represented by the following formula:
[0037]
[0038]
[0039] Among them, R 1 , R 3 At least one of the above comprises a block copolymer polyether segment represented by formula IV
[0040]
[0041] EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, 4≤m1≤15, 4≤n1≤15, R 6 , R 4 Each independently includes C 4-8 Alkylene, C 4-8 At least one of alkenylene groups.
[0042] In any embodiment, the polymer is represented by the following formula:
[0043]
[0044] Wherein, R2 comprises at least one of hydrogen, aryl, substituted or unsubstituted alkyl, and an organic segment containing an amino group or an amide group,
[0045] R 1 , R 3 At least one of the above comprises a block copolymer polyether segment represented by formula IV
[0046]
[0047] EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, 4≤m1≤50, 4≤n1≤50, and the terminal group of the polyether segment includes phenyl. In any embodiment, the weight average molecular weight of the polymer is 1000-10000, and can be 2000-5000.
[0048] The polymer with a weight average molecular weight within the above range can not only play an excellent dispersibility and further increase the solid content of the slurry, but also make the slurry have excellent flow properties, reduce the coating time, and improve the uniformity and speed of coating. The polymer with a weight average molecular weight of 2000-5000 can play a more effective dispersing role, increase the maximum solid content of the slurry, and shorten the filtration time.
[0049] The second aspect of the present application provides a method for preparing a polymer, the preparation method comprising:
[0050] The compound represented by formula VI and R 3 OH, R 1 OH, water, and a polymerizable monomer containing an unsaturated bond react to prepare a polymer having a structure shown in Formula I,
[0051]
[0052] Wherein, X comprises a phosphate group or a phosphite group, X 1 , X 2 , X 3 All contain halogen; R 1 , R 3 Each independently contains at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and R 1 , R 3 At least one of them comprises a polyether segment or a polyester segment; 2Including organic segments.
[0053] In any embodiment, the preparation method comprises the following steps:
[0054] The compound represented by formula VI and R 3 OH, R 1 OH and water undergo a first reaction to prepare an intermediate product shown in Formula VII,
[0055]
[0056] The intermediate product is subjected to a second reaction with a polymerization monomer containing at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond to prepare the polymer.
[0057] In any embodiment, the second reaction specifically comprises the following steps:
[0058] The intermediate product undergoes an addition reaction with at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, and then undergoes a substitution reaction with a halogen-substituted organic alcohol;
[0059] The polymer is prepared by cycling the addition reaction and substitution reaction in sequence for multiple times;
[0060] Among them, R 2 Containing the structure shown in formula III
[0061]
[0062] Among them, R 6 Including C 2-12 Hydrocarbon, R 7 include At least one of; wherein, q5 and q6 each independently include any integer between 0-4, 1≤n≤6.
[0063] In any embodiment, the preparation method further comprises the following steps:
[0064] The intermediate product is reacted with (i) at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, and (ii) at least one of a hydrocarbon monomer containing an unsaturated bond and a cyclic amide monomer to prepare the polymer, wherein R 2 Containing the structure shown in formula II
[0065]
[0066] Among them, R 4 With R 5 Random copolymerization, R 4 Including C 2-12 Hydrocarbon, C 3-13At least one of the amide groups, R 5 include
[0067] At least one of;
[0068] Wherein, q1, q2, q3, q4 each independently include any integer between 0 and 4, R 6 a , R 6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
[0069] Another aspect of the present application provides a method for preparing a polymer, the method comprising: reacting a compound represented by formula VI with a 3 OH, R 1 OH to prepare a polymer having a structure shown in Formula I,
[0070]
[0071] Wherein, X comprises a phosphate group or a phosphite group, X 1 , X 2 , X 3 All contain halogen; R 1 , R 3 Each independently contains at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and R 1 , R 3 At least one of the polyether segments comprises a polyether segment, and the terminal group of at least one of the polyether segments comprises an aromatic group; R 2 The third aspect of the present application provides a polymer or a polymer prepared by the preparation method of any embodiment as a dispersant.
[0072] A fourth aspect of the present application provides a positive electrode slurry, comprising a dispersant, wherein the dispersant comprises the polymer of the first aspect of claim or the polymer prepared by the preparation method of the second aspect.
[0073] The positive electrode slurry has a high solid content, which helps to improve the molding efficiency and molding quality of the positive electrode film layer, and improve the electrochemical performance and processing efficiency of the battery.
[0074] In any embodiment, the positive electrode slurry includes a positive electrode active material, and the positive electrode active material includes at least one of a lithium phosphate and a carbon-modified material thereof; optionally, the positive electrode active material includes at least one of lithium iron phosphate and a doped material thereof, lithium manganese iron phosphate and a doped material thereof, a carbon-coated material of lithium iron phosphate and a doped material thereof, and a carbon-coated material of lithium manganese iron phosphate and a doped material thereof.
[0075] The polymer is negatively charged and can further strengthen the mutual anchoring with the weakly acidic lithium-containing phosphate through electrostatic interaction, thereby improving the dispersion effect of the polymer on the lithium-containing phosphate. In addition, the lithium-containing phosphate has poor conductivity. Therefore, in the preparation process of positive electrode active materials, the method of sintering organic substances such as glucose and sucrose to coat the carbon layer is often used to improve its conductivity. The polymer also has groups that can be mutually anchored with the carbon coating layer, and also has an excellent dispersion effect on the carbon-modified lithium-containing phosphate, which can further improve the dispersibility of its slurry, thereby increasing the maximum solid content of the slurry.
[0076] In any embodiment, the positive electrode active material comprises a core and a carbon coating layer, wherein the carbon coating layer covers at least a portion of the surface of the core, wherein the carbon coating layer has a sp 2 Hybridized carbon atoms with sp 3 The molar ratio of hybridized carbon atoms is not less than 0.2, and may be not less than 0.5, and may be not less than 0.8.
[0077] The formation of a carbon coating on the surface of the core can improve the conductivity of the positive electrode active material. 2 When the molar ratio of hybridized carbon atoms to sp3 hybridized carbon atoms is not less than 0.5, the orderliness of the structure of the carbon coating layer of the positive electrode active material is relatively high, and the pore structure of the carbon coating layer has a relatively high density and a relatively small pore size distribution range. During the production process of the battery, it is difficult for external moisture to enter the pores of the carbon coating layer, thereby effectively reducing the water absorption and water storage properties of the positive electrode active material, achieving improved battery safety and cycle performance, effectively saving energy consumption during the drying process, and significantly reducing production costs.
[0078] But sp 2 Hybridized carbon atoms with sp 3 The carbon coating layer with a molar ratio of hybridized carbon atoms of not less than 0.5 has a high degree of graphitization, which makes the positive electrode active material easy to agglomerate and difficult to effectively disperse during the pulping process. The dispersant provided in the embodiment of the present application and the carbon coating layer with a high degree of graphitization have rich anchoring groups, which are particularly suitable for the dispersion of positive electrode active materials with a high degree of graphitization of the coating layer. The combination of the two can simultaneously improve the performance and processing performance of the battery.
[0079] In any embodiment, the thickness of the carbon coating layer is not greater than 15nm; optionally, the thickness of the carbon coating layer is not greater than 10nm, and optionally, the thickness of the carbon coating layer is 4nm-8nm. The carbon coating layer within the above thickness range can form a thinner carbon coating layer on the surface of the core, which can effectively improve the conductivity of the positive electrode active material and improve the compaction performance when using the positive electrode active material to prepare the battery pole piece.
[0080] In any embodiment, based on the total mass of dry materials in the positive electrode slurry, the mass content of the polymer is 0.1%-2.0%, and optionally 0.2%-1.0%.
[0081] The polymer within the above range can not only play an effective dispersing role, but also take into account the volume energy density of the battery, and will not have a serious negative impact on the electrochemical performance of the battery.
[0082] In any embodiment, the positive electrode slurry includes a binder, and the binder includes a vinylidene fluoride polymer with a weight average molecular weight of not less than 300,000. Optionally, the weight average molecular weight of the binder is 700,000-9,000,000.
[0083] Vinylidene fluoride polymers with a weight average molecular weight in this range have excellent bonding properties and electrochemical stability. The use of vinylidene fluoride polymers with a weight average molecular weight of 700,000-9 million can further reduce the amount of vinylidene fluoride used, reduce the rigidity of the positive electrode film layer, and increase the flexibility of the electrode, thereby increasing the battery's ultimate compaction density and helping to improve the battery's energy density.
[0084] In any embodiment, the maximum solid content of the positive electrode slurry is not less than 60%, and can be optionally 60%-80%.
[0085] The fifth aspect of the present application provides a positive electrode plate, which includes a positive electrode film layer, which is prepared by the positive electrode slurry of any embodiment or the positive electrode film layer includes a dispersant, and the dispersant includes the polymer of the first aspect or the polymer prepared by the preparation method of the second aspect.
[0086] In any embodiment, the positive electrode sheet has a compaction density of 2.6 g / cm 3 The number of folding times is not less than 2 times, and can be selected as 3-6 times.
[0087] The polymer can not only effectively increase the solid content of the slurry, but also act as a softener, thereby increasing the flexibility of the positive electrode and further improving the safety and electrochemical performance of the battery.
[0088] In any embodiment, the surface density of the positive electrode sheet is not less than 300 mg / 1540.25 cm 2 , optional: 300mg / 1540.25cm 2 -600 mg / 1540.25 cm 2 .
[0089] The polymer can effectively increase the maximum solid content of the slurry, increasing the coating speed by more than 30%. It is especially suitable for high-speed coating and thick coating molding methods. It can effectively solve the problem of easy cracking of the electrode during thick coating, and help to prepare positive electrode sheets with high flexibility and no cracks after winding molding.
[0090] In any embodiment, the positive electrode film layer includes a dispersant, and the dispersant includes a structure shown in Formula I,
[0091]
[0092] Wherein X comprises a phosphate group or a phosphite group, R 1 , R 3 Each independently contains at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and R 1 , R 3 At least one of them comprises a polyether segment or a polyester segment, R 2 Contains an organic segment; optionally, R 2 The organic chain segment contains at least one of an amide group and an amino group, and optionally, the end group of the polyether segment includes an aromatic group; the positive electrode active material includes at least one of lithium iron phosphate and its doping materials, lithium iron manganese phosphate and its doping materials, lithium iron phosphate and its doping materials carbon-coated materials, and lithium iron manganese phosphate and its doping materials carbon-coated materials; optionally, the positive electrode active material includes at least one of lithium iron manganese phosphate and its doping materials, lithium iron manganese phosphate and its doping materials carbon-coated materials; based on the total mass of the positive electrode film layer, the mass content of the dispersant is 0.1%-2.0%, and can be optionally 0.2%-1.0%.
[0093] The positive electrode film layer has good dispersibility and processability, which is beneficial to improving manufacturing efficiency and battery performance.
[0094] A sixth aspect of the present application provides a secondary battery, comprising the positive electrode sheet of the fifth aspect.
[0095] A seventh aspect of the present application provides an electrical device comprising the secondary battery of the sixth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0096] Figure 1 is a schematic diagram of a polymer dispersion mechanism according to one embodiment of the present application;
[0097] Figure 2 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0098] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0099] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application;
[0100] Figure 5 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0101] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0102] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0103] Description of reference numerals:
[0104] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 6 polymer; 61 anchoring group; 62 flexible chain segment; 7 positive electrode active material. DETAILED DESCRIPTION
[0105] Hereinafter, the polymer, preparation method thereof, positive electrode sheet, secondary battery, and implementation mode of the electric device of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0106] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0107] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0108] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0109] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0110] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0111] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0112] In order to improve the kinetics and electrochemical performance of the battery, the synthesis of positive electrode active materials tends to be nano-sized and more densely coated with carbon, so that the positive electrode active materials have a larger specific surface area, resulting in more solvents required for effective dispersion during the slurrying process, thereby reducing the solid content of the slurry. The slurry with low solid content needs to extend the drying time during the electrode coating and drying process, resulting in low production efficiency and high energy consumption; at the same time, the slurry with low solid content may cause problems such as edge warping, cracking and floating of the adhesive during the long heating and drying process, which deteriorates the quality of the electrode.
[0113] Based on this, the first aspect of the present application provides a polymer comprising a structure shown in formula I,
[0114]
[0115] Wherein X comprises a phosphate group or a phosphite group, R 1 , R 3 Each independently contains at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and R 1 , R 3 At least one of them comprises a polyether segment or a polyester segment; 2 Contains organic segments.
[0116] In this article, polymers include, on the one hand, a collection of macromolecules that are chemically uniform but differ in degree of polymerization, molar mass and chain length, prepared by polymerization reactions; on the other hand, they also include derivatives of such macromolecular collections formed by polymerization reactions, i.e., polymers that can be obtained by reactions of functional groups in the above-mentioned macromolecules, such as addition or substitution, and which may be chemically uniform or chemically heterogeneous.
[0117] In some embodiments, the polymer includes a phosphate polymer. The structure of the phosphate polymer is shown in Formula V:
[0118]
[0119] In some embodiments, the polymer includes a phosphite polymer. The structural formula of the phosphite polymer is shown in V':
[0120]
[0121] Herein, the polyether segment refers to a polymer segment containing an ether bond (-COC-) in the structural unit.
[0122] Herein, the polyester segment refers to a polymer segment containing an ester group (—COO—) in the structural unit.
[0123] As used herein, a hydrocarbon group refers to a group containing carbon and hydrogen atoms, including but not limited to an alkyl group, an alkenyl group, and an alkynyl group.
[0124] In this article, the organic chain segment can be a polymer of repeated structural units or an organic group formed by small molecular monomers. The dispersion mechanism of the polymer provided in the embodiment of the present application is as follows Figure 1 As shown. The polymer 6 includes an anchoring group 61 and a flexible segment 62. The anchoring group 61 at one end of the polymer 6 acts on the surface of the positive electrode active material 7, and the purpose of dispersion is achieved through the steric hindrance effect of the flexible segment 62. The phosphate group or phosphite group in the polymer 6 can be effectively anchored to the surface of the positive electrode active material 7 through intermolecular forces or electrostatic effects, and plays the role of the anchoring group 61. With the help of the anchoring effect of the anchoring group on the surface of the positive electrode active material, the steric hindrance effect of the flexible segment 62 such as the polyether segment and the polyester segment can be effectively exerted on the surface of the positive electrode active material particles, which plays a role in blocking the agglomeration of the positive electrode active material 7, thereby increasing the amount of positive electrode active material 7 that can be effectively dispersed in a unit volume of solvent, slowing down the gelation and agglomeration of the slurry during the homogenization process, reducing the slurry viscosity, significantly improving the effective solid content of the slurry, reducing the filtration time of the slurry, and improving the forming efficiency and quality of the pole piece. The polymer provided in the embodiment of the present application can make the slurry suitable for thick coating processes, which helps to improve the energy density of the battery.
[0125] At the same time, the flexible segments such as polyether segments and polyester segments in the polymer have suitable steric hindrance and low glass transition temperature, which can improve the flexibility of the electrode through the movement of the flexible segments, and simultaneously play a role of dispersion and softening.
[0126] In some embodiments, R 2 The organic chain segment contains at least one of an amide group, an amino group, and an aromatic group.
[0127] In this context, an amide group refers to The group includes both primary amides and secondary and tertiary amides.
[0128] In this context, an amino group refers to The group includes both primary amino groups and secondary and tertiary amino groups.
[0129] In this article, "aryl" refers to an organic group derived from a monocyclic or polycyclic aromatic hydrocarbon by removing a hydrogen atom. As an example, aryl includes, but is not limited to, phenyl, naphthyl, benzyl. Aryl can be unsubstituted or substituted with one or more suitable substituents.
[0130] In addition, the aromatic group can be monocyclic or polycyclic. In some embodiments, the aromatic group contains at least 6, 7, 8, 9 or 10 carbon atoms. The polymer containing the amide group is characterized by infrared absorption spectroscopy, and the carbonyl group can be observed at 1900 cm -1 ~1650cm -1 The absorption peak of the band and the amide group are located at 3500cm -1 ~3100cm -1 The band has a medium-intensity double-peak absorption peak.
[0131] The nitrogen-containing groups or aromatic groups in the polymer help to improve the anchoring effect between the polymer and the positive electrode active material, making the polymer particularly suitable for carbon-coated positive electrode active materials, further improving the versatility of the polymer as a dispersant, and more effectively exerting the dispersing effect of the polymer by increasing the anchoring sites of the dispersant, thereby further increasing the maximum solid content of the slurry, improving the quality of electrode molding, and reducing costs and increasing efficiency.
[0132] In some embodiments, R 2 The organic chain also contains C 2-12 Hydrocarbon.
[0133] In this article, “C 2-12 "Hydrocarbyl" means a straight or branched hydrocarbon chain radical consisting solely of carbon and hydrogen atoms, with or without unsaturation, having from two to twelve carbon atoms, and attached to the remainder of the molecule by at least one single bond. 2-12 Examples of hydrocarbon groups include, but are not limited to: 2-12 Alkyl, C 2-12 Alkylene, C 2-12 Alkenyl, C 2-12 Alkenylene. For example, ethylene, ethyl, n-propyl, 1-methylethyl (isopropyl), isopropylene, 1,3-propylene, butyl, isobutyl, tert-butyl, 1,4-butylene, 1,3-butylene, 2-butylene, pentyl, isopentyl, neopentyl, hexyl, heptyl, octyl, etc. The polymer contains C 2-12 The hydrocarbon group helps to further improve the anchoring effect between the polymer and the carbon-modified positive electrode active material. The hydrocarbon group can effectively anchor to the carbon on the positive electrode active material, increasing the dispersion of the anchoring sites of the polymer on the positive electrode active material, thereby further improving the application range of the polymer dispersant, increasing the maximum solid content of the slurry, optimizing the quality of electrode molding, and reducing costs and increasing efficiency.
[0134] In some embodiments, R 2 Contains the structure shown in Formula II:
[0135]
[0136] Among them, R 4 With R 5 Random copolymerization, R 4 Including C 2-12 Alkylidene, C 3-13 At least one of the amide groups, R 5 include
[0137] At least one of;
[0138] Wherein, q1, q2, q3, q4 each independently include any integer between 0 and 4, R 6 a , R 6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
[0139] C 2-12 Hydrocarbylene refers to a divalent hydrocarbon group having 2 to 12 carbon atoms; including C 2-12 Alkylene, C 2-12 As an example, C 2-12Alkylene includes, but is not limited to, 1,2-ethylene, 1,2-propylene, 1,3-propylene, 1,3-butylene, 1,4-butylene, 2-methyl-1,3-propylene, 1,1-dimethyl-1,2-ethylene, 1,4-pentylene, 1,5-pentylene, 2-methyl-1,4-butylene, 2,2-dimethyl-1,3-propylene, 1,6-hexylene, 2-methyl-1,5-pentylene 1,5-pentylene, 2,3-dimethyl-1,4-butylene, 1,7-heptylene, 2-methyl-1,6-hexylene, 3-methyl-1,6-hexylene, 2-ethyl-1,5-pentylene, 3-ethyl-1,5-pentylene, 2,3-dimethyl-1,5-pentylene, 2,4-dimethyl-1,5-pentylene, 1,8-octylene, 2-methyl-1,7-heptylene 1,7-heptanyl, 2-ethyl-1,6-hexyl, 3-ethyl-1,6-hexyl, 2,3-dimethyl-1,6-hexyl, 2,4-dimethyl-1,6-hexyl, 1,9-nonyl, 2-methyl-1,8-octanyl, 3-methyl-1,8-octanyl, 4-methyl-1,8-octanyl, 2-ethyl-1,7- heptylene, 3-ethyl-1,7-heptylene, 1,10-decylene, 2-methyl-1,9-nonylene, 3-methyl-1,9-nonylene, 4-methyl-1,9-nonylene, 5-methyl-1,9-nonylene, 1,11-undecylene, 2-methyl-1,10-decylene, 3-methyl-1,10-decylene, 5-methyl-1,10-decylene, 1,12-dodecylene.
[0140] C 2-12 Alkenylene is a divalent hydrocarbon group containing at least one double bond. 2-12 The alkenylene group includes, for example, vinylene, propenylene, 1-methylvinylene, 1-butenylene, 2-butenylene, 1-methylpropenylene, 2-methylpropenylene, 1-pentenylene, 2-pentenylene, 1-methyl-1-butenylene, 1-methyl-2-butenylene, 1-hexenylene, 2-hexenylene, 3-hexenylene, 1-methyl-1-pentenylene, 1-methyl-2-pentenylene, 1-methyl-3-pentenylene, 1,4-dimethyl-1-butenylene, 1,4-dimethyl-2-butenylene, 1-heptenylene, 2-heptenylene, 3-heptenylene, 1-octenylene, 2-octenylene, 3-octenylene.
[0141] In some embodiments, C 3-13 Amide groups include the following groups:
[0142] Here, x is 2 to 12, and can be selected from 2 to 5.
[0143] In some embodiments, x is 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12.
[0144] In this paper, C 1-4 The alkyl group includes at least one of a methyl group, an ethyl group, a propyl group, an isopropyl group, a 2-methyl-1-propyl group, and a 2-methyl-2-propyl group.
[0145] In some embodiments, s is any one of 1, 2, 3, 4, 5, and 6.
[0146] In some embodiments, t is any one of 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0147] In some embodiments, q1, q2, q3, q4 are each independently selected from 0, 1, 2, 3 or 4.
[0148] The organic chain segments of the above structure include nitrogen-containing groups and alkylene groups, which can play an anchoring role more effectively, enhance the dispersion effect of the polymer, and effectively increase the solid content of the slurry.
[0149] In some embodiments, R 2 Containing the structure shown in formula III
[0150]
[0151] Among them, R 6 Including C 2-12 Alkylene, R 7 include At least one of; wherein, q5 and q6 each independently include any integer between 0-4, 1≤n≤6.
[0152] In some embodiments, q5 and q6 each independently include 0, 1, 2, 3 or 4.
[0153] In some embodiments, n is any one of 1, 2, 3, 4, 5, and 6.
[0154] The organic chain segments of the above structure can more effectively play an anchoring role through the alternating arrangement of nitrogen-containing groups and alkylene groups, enhance the dispersion effect of the polymer, and effectively increase the solid content of the slurry.
[0155] In some embodiments, R 2 The terminal groups contain -C(O)-NH 2 、-CH 2 -NH 2 At least one of.
[0156] The terminal group contains -C(O)-NH 2 、-CH2 -NH 2 The polymer can play a more effective dispersing role, increase the maximum solid content of the slurry, and thus improve the molding quality and efficiency of the pole piece.
[0157] In some embodiments, R 1 , R 3 At least one of them comprises a polyether segment, optionally, R 1 and R 3 The polymers containing polyether segments were characterized by infrared absorption spectroscopy, and the ether bond absorption peak was observed to be located at 1250-1100 cm -1 Band.
[0158] In some embodiments, R 2 Includes at least one of H and aryl.
[0159] In some embodiments, R 1 , R 3 One of them contains a polyether segment and the other contains C 1-4 alkyl.
[0160] In some embodiments, R 1 and R 3 All of them include polyether segments.
[0161] R 1 and R 3 Compared with R 1 , R 3 One of them contains a polyether segment and the other contains C 1-4 Alkyl and polymer further optimize the filterability of the slurry and further improve the flexibility of the electrode.
[0162] In some embodiments, R 1 , R 3 At least one of the polyether segments comprises a polyether segment of formula IV
[0163]
[0164] EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, 4≤m1≤50, 4≤n1≤50.
[0165] In some embodiments, the polyether segment is a block copolymer segment. In some embodiments, the polyether segment is a random copolymer segment.
[0166] In some embodiments, m1 and n1 can be independently selected from 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20, 25, 30, 35, 40, 45, 50 or any value therebetween.
[0167] The polyether segment with the above structure has suitable steric hindrance and low glass transition temperature, which can more effectively reduce the order and glass transition temperature of the binder crystallization in the positive electrode slurry, thereby reducing the crystallinity of the binder and improving the flexibility of the electrode. Through the effects of dispersion and flexibility, the uniformity and flexibility of the electrode are improved, thereby improving the safety performance and ultimate compaction density of the battery, so that the positive electrode active material loading of the battery can be increased, which helps to further improve the energy density of the battery.
[0168] In some embodiments, the end groups of the polyether segments include aromatic groups.
[0169] The aromatic group has excellent compatibility with the carbon layer on the surface of the positive electrode active material, which helps to further improve the anchoring effect between the polymer and the carbon-modified positive electrode active material. With the help of the aromatic group and the carbon on the positive electrode active material, the anchoring site dispersion of the polymer on the positive electrode active material can be effectively anchored, thereby further improving the application range of the polymer dispersant, increasing the maximum solid content of the slurry, optimizing the quality of the pole piece molding, and reducing costs and increasing efficiency. In some embodiments, X includes a phosphate group.
[0170] Phosphate polymers can more effectively increase the solid content of the slurry, shorten the filtration time, and improve the flexibility of the electrode; and phosphate polymers have better stability, and can effectively improve the battery's cycle capacity retention rate on the basis of improving the slurry's dispersibility.
[0171] In some embodiments, the polymer includes at least one of the following polymers:
[0172]
[0173] Among them, R 1 , R 3 At least one of the above comprises a block copolymer polyether segment represented by formula IV
[0174]
[0175] EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, 4≤m1≤15, 4≤n1≤15.
[0176] In some embodiments, R 6 , R4 Each independently includes C 4-8 Alkylene, C 4-8 At least one of alkenylene groups.
[0177] In some embodiments, R 6 , R 4 Each independently comprises -(CH 2 ) 4 -、-(CH 2 ) 5 -、-(CH 2 ) 6 -、-(CH 2 ) 7 -、-(CH 2 ) 8 -、 At least one of the groups.
[0178] In some embodiments, the end groups of the polyether segments include phenyl groups.
[0179] In some embodiments, the polymer is represented by the following formula:
[0180]
[0181] Wherein, R2 comprises at least one of hydrogen, aryl, substituted or unsubstituted alkyl, and an organic segment containing an amino group or an amide group, and R 1 , R 3 At least one of them comprises a block copolymer polyether segment represented by formula IV,
[0182]
[0183] EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, 4≤m1≤50, 4≤n1≤50, and the terminal group of the polyether segment includes phenyl.
[0184] In some embodiments, the weight average molecular weight of the polymer is 1,000-10,000, optionally 2,000-5,000.
[0185] The weight average molecular weight has a meaning known in the art and can be measured by methods known in the art. As an example, the weight average molecular weight can be measured by gel chromatography.
[0186] In some embodiments, the weight average molecular weight of the polymer is 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, or any value therebetween.
[0187] The polymer with a weight average molecular weight within the above range can not only play an excellent dispersibility and further increase the solid content of the slurry, but also make the slurry have excellent flow properties, reduce the coating time, and improve the uniformity and speed of coating. The polymer with a weight average molecular weight of 2000-5000 can play a more effective dispersing role, increase the maximum solid content of the slurry, and shorten the filtration time.
[0188] The second aspect of the present application provides a method for preparing a polymer, the preparation method comprising the following steps:
[0189] The compound represented by formula VI and R 3 OH, R 1 OH, water, and a polymerizable monomer containing an unsaturated bond react to prepare a polymer having a structure shown in Formula I,
[0190]
[0191] Wherein, X comprises a phosphate group or a phosphite group, X 1 , X 2 , X 3 All contain halogen; R 1 , R 3 Each independently contains at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and R 1 , R 3 At least one of them comprises a polyether segment or a polyester segment; 2 Including organic segments.
[0192] Herein, the halogen includes at least one of fluorine, chlorine, bromine and iodine.
[0193] In some embodiments, phosphorus and oxygen in Formula VI are connected via a double bond, and X in Formula I is a phosphate group.
[0194] In some embodiments, Formula VI does not include oxygen and X in Formula I is a phosphite group.
[0195] In some embodiments, Formula VI includes POCl 3 or PCl 3 .
[0196] In some embodiments, the preparation method comprises the following steps:
[0197] The compound represented by formula VI and R 3 OH, R 1OH and water undergo a first reaction to prepare an intermediate product shown in Formula VII,
[0198]
[0199] The intermediate product is subjected to a second reaction with a polymerization monomer containing at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond to prepare the polymer.
[0200] In some embodiments, the first reaction specifically comprises:
[0201] Add R to the compound represented by Formula VI under stirring. 3 OH, keep the reaction temperature below 20°C, stir for a while, raise the temperature to 40-50°C, react for 6-7 hours, add water, react at 50-60°C for 3-4 hours to obtain the first intermediate product shown in formula A. 3 The molar ratio of OH to the compound of formula VI is 1.2-1.5, wherein R 3 Including C 1-4 alkyl,
[0202]
[0203] The above reaction conditions are conducive to improving the purity of the product.
[0204] In some embodiments, the first reaction further comprises:
[0205] The polyether and the first intermediate product are reacted at 100° C. to 120° C. for 4 h to 7 h to generate an intermediate product shown in Formula VII, wherein R 1 Contains polyether segments.
[0206] In some embodiments, the second reaction specifically comprises the following steps:
[0207] The intermediate product undergoes an addition reaction with at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, and then undergoes a substitution reaction with a halogen-substituted organic alcohol;
[0208] The polymer is prepared by cycling the addition reaction and substitution reaction for multiple times;
[0209] Among them, R 2 Containing the structure shown in formula III
[0210]
[0211] Among them, R 6 Including C 2-12 Hydrocarbon, R 7 include At least one of; wherein, q5 and q6 each independently include any integer between 0-4, 1≤n≤6.
[0212] An addition reaction is a reaction in which the π bond in a double bond is broken to form two single bonds.
[0213] Substitution reaction refers to a type of chemical reaction in which an atom or group replaces a certain atom or group in an organic molecule and takes its place.
[0214] In some embodiments, the preparation method further comprises the following steps:
[0215] The intermediate product is reacted with (i) at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, and (ii) at least one of a hydrocarbon monomer containing an unsaturated bond and a cyclic amide monomer to prepare the polymer, wherein R 2 Containing the structure shown in formula II
[0216]
[0217] Among them, R 4 With R 5 Random copolymerization, R 4 Including C 2-12 Hydrocarbon, C 3-13 At least one of the amide groups, R 5 include
[0218] At least one of;
[0219] Wherein, q1, q2, q3, q4 each independently include any integer between 0 and 4, R 6 a , R 6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
[0220] In some embodiments, the hydrocarbon monomer containing an unsaturated bond comprises at least one of an olefin monomer, an alkyne monomer, and a cyclic alkane.
[0221] In some embodiments, a cyclic amide monomer refers to a cyclic monomer including an amide bond.
[0222] In some embodiments, the third reaction specifically comprises mixing the intermediate product with at least one of a hydrocarbon monomer containing an unsaturated bond and a cyclic amide monomer, reacting the mixture for a period of time, and then adding at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond to cause a copolymerization reaction.
[0223] In some embodiments, the preparation method further comprises the following steps:
[0224] The polymer having a terminal group of hydroxyl group is subjected to a capping reaction with an unsaturated monomer containing an amide group or an amino group to prepare a polymer having a terminal group containing an amide group or an amino group.
[0225] The present application provides a method for preparing a polymer, the preparation method comprising:
[0226] The compound represented by formula VI and the compound containing R 3 OH, R 1 OH to prepare a polymer having a structure shown in Formula I,
[0227]
[0228] Wherein, X comprises a phosphate group or a phosphite group, X 1 , X 2 , X 3 All contain halogen; R 1 , R 3 Each independently contains at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and R 1 , R 3 At least one of the polyether segments comprises a polyether segment, and the terminal group of at least one of the polyether segments comprises an aromatic group; R 2 Including organic segments.
[0229] In some embodiments, the monomer represented by formula VI is combined with R 1 OH, R 3 After OH reacts in an inert, alkaline environment, water or phenol is added to react to obtain a polymer.
[0230] In some embodiments, the polymer containing a hydroxyl group in R2 is further subjected to a second reaction with a polymerizable monomer containing at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond to prepare a polymer containing nitrogen in R2.
[0231] In some embodiments, the polymer according to any embodiment of the present application and the polymer prepared by the preparation method according to any embodiment of the present application are used as a dispersant.
[0232] In some embodiments, the polymer of any embodiment of the present application and the polymer prepared by the preparation method of any embodiment of the present application are used as a dispersant in secondary battery electrode slurry.
[0233] In some embodiments, the polymer according to any embodiment of the present application and the polymer prepared by the preparation method according to any embodiment of the present application are used as a dispersant in a positive electrode slurry of a secondary battery.
[0234] [Cathode slurry]
[0235] A third aspect of the present application provides a positive electrode slurry, wherein the positive electrode slurry includes a dispersant, and the dispersant includes a polymer in any embodiment or a polymer prepared by a preparation method in any embodiment.
[0236] The positive electrode slurry has a high solid content, which helps to improve the molding efficiency and molding quality of the positive electrode film layer, and improve the electrochemical performance and processing efficiency of the battery.
[0237] In some embodiments, the positive electrode slurry includes a positive electrode active material, and the positive electrode active material includes at least one of a lithium-containing phosphate and a carbon-modified material thereof.
[0238] In some embodiments, the lithium-containing phosphate includes at least one of lithium iron phosphate and its doping materials, lithium iron manganese phosphate and its doping materials. In some embodiments, the doping material includes a doping material at any site, which can be lithium doping, phosphorus doping, manganese doping, and iron doping.
[0239] In some embodiments, the carbon-modified material includes at least one of a carbon-coated material and a carbon-doped material.
[0240] In some embodiments, the positive electrode active material includes at least one of lithium iron phosphate and its doped materials, lithium iron manganese phosphate and its doped materials, carbon-coated materials of lithium iron phosphate and its doped materials, and carbon-coated materials of lithium iron manganese phosphate and its doped materials.
[0241] The polymer is negatively charged and can further strengthen the mutual anchoring with the weakly acidic lithium-containing phosphate through electrostatic interaction, thereby improving the dispersion effect of the polymer on the lithium-containing phosphate. In addition, the lithium-containing phosphate has poor conductivity. Therefore, in the preparation process of positive electrode active materials, the method of sintering organic substances such as glucose and sucrose to coat the carbon layer is often used to improve its conductivity. The polymer also has groups that can be mutually anchored with the carbon coating layer, and also has an excellent dispersion effect on the carbon-modified lithium-containing phosphate, which can further improve the dispersibility of its slurry, thereby increasing the maximum solid content of the slurry.
[0242] In some embodiments, the positive electrode active material includes a core and a carbon coating layer, wherein the carbon coating layer covers at least a portion of the surface of the core, wherein the carbon coating layer has a sp 2 Hybridized carbon atoms with sp 3 The molar ratio of hybridized carbon atoms is not less than 0.2, and may be not less than 0.5, and may be not less than 0.8.
[0243] In some embodiments, the sp2 hybridized carbon atoms in the carbon coating layer are 3 The molar ratio of hybridized carbon atoms can be selected as 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or any range therebetween.
[0244] The carbon structure and characteristics of the carbon coating layer can be determined by methods known in the art. As an example, it can be determined by Raman spectroscopy. Specifically, first measure the Raman spectrum of the positive electrode active material, and obtain Ig / Id (where Id is sp 3 Peak intensity of hybridized carbon atoms, Ig is sp 2 The peak intensity of the hybridized carbon atom is sp 2 The peak height of hybridized carbon atoms is related to sp 3 hybridized carbon atom peak height ratio), thereby obtaining sp 2 Hybridized carbon with sp 3 The molar ratio of hybrid carbon. sp in the carbon coating layer of the positive electrode active material 2 Hybridized carbon atoms with sp 3 The molar ratio of hybridized carbon atoms is not particularly limited. For example, the sp 2 Hybridized carbon atoms with sp 3 The molar ratio of hybridized carbon atoms may be not less than 0.5. In some embodiments, the sp 2 Hybridized carbon atoms with sp 3 The molar ratio of hybridized carbon atoms may be not less than 0.8. 2 Hybridized carbon atoms with sp 3 When the molar ratio of hybridized carbon atoms is within the above range, the carbon coating on the surface of the inner core has a higher degree of graphitization and a denser structure, which can not only reduce the water absorption of the carbon coating, but also enable the carbon coating to achieve good conductivity, thereby ensuring the passage of lithium ions and being beneficial to improving the cycle performance and safety performance of the positive electrode active material.
[0245] In some embodiments, the core includes a phosphate; in some embodiments, the phosphate includes at least one of lithium manganese phosphate, lithium iron phosphate, lithium manganese iron phosphate, and doped materials thereof.
[0246] The formation of a carbon coating on the surface of the core can improve the conductivity of the positive electrode active material. 2 When the molar ratio of hybridized carbon atoms to sp3 hybridized carbon atoms is not less than 0.5, the orderliness of the structure of the carbon coating layer of the positive electrode active material is relatively high, and the pore structure of the carbon coating layer has a relatively high density and a relatively small pore size distribution range. During the production process of the battery, it is difficult for external moisture to enter the pores of the carbon coating layer, thereby effectively reducing the water absorption and water storage properties of the positive electrode active material, achieving improved battery safety and cycle performance, effectively saving energy consumption during the drying process, and significantly reducing production costs.
[0247] But sp 2 Hybridized carbon atoms with sp3 The carbon coating layer with a molar ratio of hybridized carbon atoms of not less than 0.5 has a high degree of graphitization, which makes the positive electrode active material easy to agglomerate and difficult to effectively disperse during the pulping process. The dispersant provided in the embodiment of the present application and the carbon coating layer with a high degree of graphitization have rich anchoring groups, which are particularly suitable for the dispersion of positive electrode active materials with a high degree of graphitization of the coating layer. The combination of the two can simultaneously improve the performance and processing performance of the battery.
[0248] In some embodiments, the core includes Li 1+x Mn 1-y A y P 1-z R z O 4 , x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from B (boron), S, Si and N. The manganese-doping element A selected from the above elements helps to reduce the lattice change rate of lithium manganese phosphate in the process of lithium insertion and extraction, improves the structural stability of the positive electrode active material, greatly reduces the dissolution of manganese and reduces the oxygen activity on the surface of the particles; the phosphorus-doping element R selected from the above elements also helps to change the difficulty of the Mn-O bond length change, thereby improving the electronic conductivity and reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the rate performance of the secondary battery.
[0249] Unless otherwise specified, in the chemical formula of the above core, when a doping site has two or more elements, the above numerical ranges for x, y, z or m are not only limited to the stoichiometric number of each element as the site, but also to the sum of the stoichiometric numbers of the elements as the site. 1+x Mn 1- y AHr 1-z R z O 4 When A is more than two elements A1, A2...An, the stoichiometric numbers y1, y2...yn of A1, A2...An must each fall within the numerical range of y defined in this application, and the sum of y1, y2...yn must also fall within the numerical range. Similarly, for the case where R is more than two elements, the numerical range of the stoichiometric number of R defined in this application also has the above meaning.
[0250] According to some embodiments of the present application, the type of the core is not particularly limited. For example, the core may include Li 1+ x C m Mn 1-y A y P 1-z R z O 4-n D n , the size of x is affected by the valence of A and R and the sizes of y and z to ensure that the entire system is electrically neutral. If the value of x is too small, the lithium content of the entire core system will be reduced, affecting the gram capacity of the material. More specifically, x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, n is any value in the range of 0.001 to 0.1, and m is any value in the range of 0.9 to 1.1. For example, 1+x is selected from the range of 0.9 to 1.1, for example, 0.97, 0.977, 0.984, 0.988, 0.99, 0.991, 0.992, 0.993, 0.994, 0.995, 0.996, 0.997, 0.998, 1.01, x is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, y is selected from the range of 0.001 to 0.5, for example, 0.001 , 0.005, 0.02, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.34, 0.345, 0.349, 0.35, 0.4, z is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, 0.08, 0.1, n is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, 0.08, 0.1, and the positive electrode active material is electrically neutral. C includes one or more elements of Zn, Al, Na, K, Mg, Nb, Mo and W, A includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, R includes one or more elements of B (boron), S, Si and N, and D includes one or more elements of S, F, Cl and Br. By doping specific elements at the Li position, Mn position, P position and O position of the compound at the same time in a specific amount, significantly improved rate performance can be obtained, while the dissolution of Mn and the doping elements at the Mn position is significantly reduced, significantly improved cycle performance and / or high temperature stability are obtained, and the gram capacity and compaction density of the positive electrode active material can also be improved.
[0251] In some embodiments, the thickness of the carbon coating layer is not greater than 15 nm; optionally, the thickness of the carbon coating layer is not greater than 10 nm; optionally, the thickness of the carbon coating layer is 4 nm-8 nm.
[0252] In some embodiments, the thickness of the carbon coating layer may be 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, or any range therebetween.
[0253] The thickness of the carbon coating can be tested as follows: a thin slice of about 100 nm thick is cut from the middle of a single particle of the positive electrode active material by FIB, and then the slice is tested by transmission electron microscopy (TEM) to obtain the original TEM test image and save the original image format (xx.dm3). The original image obtained by the above TEM test is opened in the Digital Micrograph software, and the carbon coating is identified by the lattice spacing and angle information, and the thickness of the carbon coating is measured. The thickness of the selected particle is measured at three positions and the average value is taken.
[0254] The carbon coating layer within the above thickness range can form a thinner carbon coating layer on the surface of the inner core, which can effectively improve the conductivity of the positive electrode active material and improve the compaction performance when the positive electrode active material is used to prepare a battery pole piece.
[0255] In some embodiments, the positive electrode active material is prepared by the following method:
[0256] Providing an inner core; forming a carbon coating layer on at least a portion of the surface of the inner core, wherein the molar ratio of sp2 hybridized carbon atoms to sp3 hybridized carbon atoms in the carbon coating layer is not less than 0.2, and optionally not less than 0.5.
[0257] In some embodiments, forming a carbon coating layer on at least a portion of the surface of the inner core includes: forming a pre-carbon coating layer on the inner core surface through a carbon source to obtain a pre-coated positive electrode active material; sintering the pre-coated positive electrode active material to form the carbon coating layer to obtain the positive electrode active material, and the carbon source includes a first carbon source and a second carbon source.
[0258] In some embodiments, a pre-carbon coating layer is formed on the surface of the inner core to obtain a pre-coated positive electrode active material. The method for forming the pre-carbon coating layer on the surface of the inner core is not particularly limited. For example, the carbon source and the inner core can be placed in the same reaction container, and the carbon source can react on the surface of the inner core by hydrothermal treatment, thereby forming a carbon coating layer on the surface of the inner core; the carbon source and the inner core can also be placed in a ball milling device, such as a sand mill, and the carbon source can be mechanically mixed to form a carbon coating layer on the surface of the inner core. In some embodiments, the carbon source includes a first carbon source and a second carbon source, and the first carbon source includes at least one of polyvinyl alcohol, polyethylene glycol and citric acid; the second carbon source includes at least one of starch, sucrose and glucose. In some embodiments, the molecular weight of the first carbon source is not less than 1000, and in other embodiments, the molecular weight of the first carbon source can be 2000-5000. Thus, a pre-carbon coating layer with uniform distribution and relatively uniform thickness can be formed on the surface of the inner core by ball milling, which is conducive to forming a dense and uniform carbon coating layer pore structure after sintering. In some embodiments, the second carbon source can include at least one of starch, sucrose and glucose. In some embodiments, the second carbon source can be glucose.
[0259] In some embodiments, the pre-coated positive electrode active material is sintered under an inert gas atmosphere. In some embodiments, the pre-coated positive electrode active material is sintered to obtain the positive electrode active material. The sintering treatment should be carried out under an inert atmosphere to avoid oxidation reaction of the carbon source so that a carbon coating layer with a high degree of graphitization cannot be obtained. The type of inert gas is not particularly limited. For example, the inert gas may include at least one of nitrogen and helium. The conditions of the sintering treatment are not particularly limited. For example, the temperature of the sintering treatment may be 650°C-800°C, and the time of the sintering treatment may be 6h-12h. Thus, a carbon coating layer with a high degree of graphitization can be formed on the surface of the inner core. As the temperature of the sintering treatment increases, the degree of graphitization of carbon in the carbon coating layer also increases. The degree of graphitization of the carbon coating layer can be effectively controlled by controlling the highest sintering treatment of the sintering treatment, and the carbon coating layer has a dense pore structure and better conductivity.
[0260] In some embodiments, forming a carbon coating layer on at least a portion of the surface of the inner core includes: mixing the inner core with a first carbon source and obtaining a first coated positive electrode active material through a first sintering treatment; mixing the first coated positive electrode active material with a second carbon source and obtaining the positive electrode active material through a second sintering treatment.
[0261] In some embodiments, the temperature of the first sintering process is 350°C-800°C, and the time of the first sintering process is 6h-12h. In some embodiments, the temperature of the second sintering process is 650°C-850°C, and the time of the second sintering process is 6h-24h.
[0262] In some embodiments, based on the total mass of dry materials in the positive electrode slurry, the mass content of the polymer is 0.1%-2.0%, and optionally 0.2%-1.0%.
[0263] In some embodiments, based on the total mass of the dry material of the positive electrode slurry, the mass content of the polymer can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% or any value therebetween. The polymer within the above range can not only play an effective dispersing role, but also take into account the volume energy density of the battery, and will not have a serious negative impact on the electrochemical performance of the battery.
[0264] In some embodiments, the positive electrode slurry includes a binder, and the binder includes a vinylidene fluoride polymer with a weight average molecular weight of not less than 300,000. Optionally, the weight average molecular weight of the binder is 700,000-9,000,000.
[0265] In some embodiments, the vinylidene fluoride polymer is a vinylidene fluoride homopolymer.
[0266] In some embodiments, the vinylidene fluoride polymer is a vinylidene fluoride copolymer.
[0267] The weight average molecular weight has a well-known meaning in the art and can be measured by any well-known method. In some embodiments, the weight average molecular weight of the binder is characterized by gel chromatography.
[0268] In some embodiments, the weight average molecular weight of the binder can be selected to be 700,000, 1,000,000, 2,000,000, 3,000,000, 4,000,000, 5,000,000, 6,000,000, 7,000,000, 8,000,000, 9,000,000, or any value therebetween.
[0269] Vinylidene fluoride polymers with a weight average molecular weight in this range have excellent bonding properties and electrochemical stability. The use of vinylidene fluoride polymers with a weight average molecular weight of 700,000-9 million can further reduce the amount of vinylidene fluoride used, reduce the rigidity of the positive electrode film layer, and increase the flexibility of the electrode, thereby increasing the battery's ultimate compaction density and helping to improve the battery's energy density.
[0270] In some embodiments, the maximum solid content of the positive electrode slurry is not less than 60%, and can be optionally 60%-80%.
[0271] The maximum solid content of the positive electrode slurry refers to the maximum solid content of the slurry that meets the shipping viscosity between 4000 and 35000mpa.s and does not gel after the positive electrode slurry is left to stand for 24 hours. The actual solid content test method of the positive electrode slurry is to take the slurry weight and record it as m 0 , placed in a weight loss tester; the slurry is evaporated until the weight loss rate is less than 0.3%, and the remaining weight is recorded as m 1 ; Solid content = m 1 / m 0 *100%.
[0272] In some embodiments, the maximum solid content of the positive electrode slurry may be 60%, 65%, 70%, 75%, 80% or any value therebetween.
[0273] By adding polymers to the positive electrode slurry, the solid content and flexibility of the slurry are effectively increased, and the flexibility and molding efficiency of the electrode are improved.
[0274] [Positive electrode]
[0275] The present application also provides a positive electrode plate, which includes a positive electrode film layer, which is prepared by the positive electrode slurry of any embodiment or the positive electrode film layer includes a dispersant, and the dispersant includes a polymer of any embodiment or a polymer prepared by the preparation method of any embodiment.
[0276] In some embodiments, the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0277] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0278] In some embodiments, the positive electrode sheet has a compaction density of 2.6 g / cm 3 The number of folding times is not less than 2 times, and can be selected as 3-6 times.
[0279] The compacted density of the positive electrode is 2.6g / cm 3 The number of times the electrode can be folded can be used to characterize the flexibility of the electrode, and can be measured by any known method. As an example, a defect-free electrode with a compaction density of 2.6 g / cm 3The positive electrode sheet is cut into samples with a length and width of 25cm*4cm along the longitudinal direction. The number of samples is ≥4. After pre-folding it in the longitudinal direction (25cm direction), the film is placed on the test platform and rolled once with a 2kg cylindrical roller. If it is light-transmitting, the number of times of brittle light transmission is 1. If it is not light-transmitting, repeat the reverse folding and rolling. Observe the crease against the light to see if it is light-transmitting or broken, record the actual number of folds, test 4 times, and take the average as the test result.
[0280] In some embodiments, the positive electrode sheet has a compaction density of 2.6 g / cm 3 The number of folds that can be selected is 2, 3, 4, 5 or 6.
[0281] The polymer can not only effectively increase the solid content of the slurry, but also act as a softener, thereby increasing the flexibility of the positive electrode and further improving the safety and electrochemical performance of the battery.
[0282] In some embodiments, the surface density of the positive electrode sheet is not less than 300 mg / 1540.25 cm 2 , optional: 300mg / 1540.25cm 2 -600 mg / 1540.25 cm 2 .
[0283] In some embodiments, the surface density of the positive electrode sheet is 300 mg / 1540.25 cm 2 , 400mg / 1540.25cm 2 、450mg / 1540.25cm 2 、500mg / 1540.25cm 2 、600mg / 1540.25cm 2 The surface density of the pole piece has a well-known meaning and can be measured by any well-known method.
[0284] In some embodiments, the positive electrode plate comprises lithium iron phosphate, and the surface density of the positive electrode plate is not less than 360 mg / 1540.25 cm 2 , optional: 360mg / 1540.25cm 2 -600mg / 1540.25cm 2 .
[0285] In some embodiments, the positive electrode plate comprises lithium iron manganese phosphate, and the surface density of the positive electrode plate is not less than 300 mg / 1540.25 cm 2 , optional: 300mg / 1540.25cm 2 -600mg / 1540.25cm 2 .
[0286] The polymer can effectively increase the maximum solid content of the slurry, increasing the coating speed by more than 30%. It is especially suitable for high-speed coating and thick coating molding methods. It can effectively solve the problem of easy cracking of the electrode during thick coating, and help to prepare positive electrode sheets with high flexibility and no cracks after winding molding.
[0287] In some embodiments, the positive electrode film layer includes a dispersant, and the dispersant includes a structure shown in Formula I,
[0288]
[0289] Wherein X comprises a phosphate group or a phosphite group, R 1 , R 3 Each independently contains at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and R 1 , R 3 At least one of them comprises a polyether segment or a polyester segment, R 2 Contains an organic segment; optionally, R 2 The organic chain segment contains at least one of an amide group and an amino group; optionally, the end group of the polyether segment includes an aromatic group; the positive electrode active material includes at least one of lithium iron phosphate and its doping materials, lithium iron manganese phosphate and its doping materials, lithium iron phosphate and its doping materials carbon-coated materials, and lithium iron manganese phosphate and its doping materials carbon-coated materials; optionally, the positive electrode active material includes at least one of lithium iron manganese phosphate and its doping materials, lithium iron manganese phosphate and its doping materials carbon-coated materials, based on the total mass of the positive electrode film layer, the mass content of the dispersant is 0.1%-2.0%, and can be optionally 0.2%-1.0%.
[0290] The positive electrode film layer has good dispersibility and processability, which is conducive to the simultaneous improvement of manufacturing efficiency and battery performance. In some embodiments, the positive electrode film layer may also optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0291] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder, and the dispersant are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0292] [Negative electrode]
[0293] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0294] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0295] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0296] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0297] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0298] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0299] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0300] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0301] [Electrolytes]
[0302] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0303] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0304] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0305] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0306] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0307] [Isolation film]
[0308] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0309] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0310] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0311] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0312] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0313] [Secondary battery]
[0314] Another aspect of the present application provides a secondary battery, the secondary battery comprising the positive electrode sheet of any embodiment.
[0315] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example. The secondary battery may also be a sodium ion battery, a magnesium ion battery, or a potassium ion battery.
[0316] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0317] [Battery module]
[0318] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0319] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0320] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0321] [Battery Pack]
[0322] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0323] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0324] [Electrical devices]
[0325] In one embodiment of the present application, there is provided an electric device, comprising at least one of a secondary battery of any embodiment, a battery module of any embodiment, or a battery pack of any embodiment.
[0326] The electrical device includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0327] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0328] Figure 7The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0329] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0330] Example
[0331] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0332] Example 1
[0333] 1) Preparation of dispersant:
[0334] Preparation of the first intermediate
[0335] Add POCl into a four-necked flask equipped with a thermometer, stirrer and hydrogen chloride gas collection device. 3 , add R dropwise while stirring 3 OH, keep the reaction temperature below 20°C, stir for 20 minutes and then heat to 40-50°C, where n(POCl 3 ):n(R 3 -OH) is 1.2-1.5, after reacting for 6-7 hours, a certain amount of distilled water is added dropwise to the system, and the reaction is carried out at 55°C for 3.5 hours to prepare the first intermediate product. The yield of the first intermediate product can be ≥95% by controlling the reaction parameters, wherein R 3 -CH 2 CH 3 .
[0336]
[0337] Preparation of the second intermediate product:
[0338] Weigh 1,2-propylene glycol (0.4% of the total mass of ethylene oxide, propylene oxide monomer, and the first intermediate product) and concentrated sulfuric acid (0.3% of the total mass) into the reactor, close the reactor cover, and tighten the fixing bolts with a wrench. Evacuate the reactor and replace it with high-purity nitrogen three times, then add ethylene oxide and propylene oxide in turn, with a molar ratio of n 2 :m 2, block polymerization reaction was carried out, the pressure during the reaction was maintained at 0.3±0.05MPa, the temperature was maintained at 115±5℃, the first intermediate product was added after the reaction for 5h, and the second intermediate product was generated after the reaction was carried out at 115±5℃ for 5h. The schematic diagram of the reaction process is shown below, where A 1 for n2 is 25, m2 is 25, R 3 -CH 2 CH 3 .
[0339]
[0340] Preparation of polymer:
[0341] The second intermediate product was reacted with acrylamide at room temperature for 12 hours, and then HO(CH 2 ) 4 Cl undergoes substitution reaction under alkaline conditions at room temperature for 6 hours, and then the above addition reaction and substitution reaction are cycled once to prepare R in the figure below 6 For -(CH 2 ) 4 -, the product represented by formula X, wherein n is 2. The weight average molecular weight of the polymer is 3109.
[0342]
[0343] 2) Preparation of positive electrode slurry:
[0344] The positive electrode active material carbon-coated lithium iron phosphate (LFP@C), conductive agent carbon black (SP), binder polyvinylidene fluoride (PVDF), and dispersant (the above polymer) were added to N-methylpyrrolidone (NMP) at a mass ratio of 96.5:2:1:0.5. The mass fraction of the dispersant was 0.5% of the dry material in the slurry, and the weight average molecular weight of PVDF was 700,000. 2 Hybridized carbon atoms with sp 3 The molar ratio of hybridized carbon atoms is 0.271.
[0345] 3) Preparation of positive electrode sheet:
[0346] The positive electrode slurry is evenly coated on the two surfaces of the aluminum foil positive electrode current collector, and then dried to obtain a film layer; after that, it is cold pressed and cut to obtain a positive electrode sheet, and the surface density of the positive electrode sheet is 450mg / 1540.25mm 2 .
[0347] 4) Preparation of negative electrode sheet
[0348] The negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a weight ratio of 96:2:1:1, and mixed evenly to prepare the negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil for multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0349] 5) Isolation film
[0350] Polypropylene film is used as the isolation film.
[0351] 6) Preparation of electrolyte
[0352] In an argon atmosphere glove box (H 2 O<0.1ppm, O 2 <0.1ppm), organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 3 / 7, and LiPF 6 The lithium salt is dissolved in an organic solvent to prepare a solution with a mass content of 12.5% to obtain an electrolyte.
[0353] 7) Preparation of secondary batteries
[0354] The positive electrode sheet, separator, and negative electrode sheet prepared in Example 1 are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, and the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain the lithium-ion battery product of Example 1.
[0355] Example 2
[0356] The preparation method is similar to that of Example 1, except that the type of dispersant is changed. The first two steps of the dispersant synthesis process are consistent with those of Example 1. The nitrogen-containing monomer added in the third step is 3-amino-1-propylene. The dispersant structural formula is as follows, wherein R 1 , R 3 , R 6 , n remain the same as in Example 1.
[0357]
[0358] Example 3
[0359] The preparation method is similar to that of Example 1, except that the type of dispersant is changed. The first two steps of the dispersant synthesis process are consistent with those of Example 1, and the preparation process of the third step polymer is as follows:
[0360] Butadiene was added to the second intermediate product and reacted at 100°C for 0.5h, then acrylamide was added and reacted at 110°C in an alkaline environment for 6h to obtain a polymer. The reaction schematic diagram is shown in the figure below, where R 1 , R 3 As in Example 1, s is 3, t is 3, the structural unit derived from butadiene and the structural unit derived from acrylamide are random copolymers,
[0361]
[0362] Example 4
[0363] The preparation method is similar to that of Example 1, except that the type of dispersant is changed. The first two steps of the dispersant synthesis process are consistent with those of Example 1, and the preparation process of the third step polymer is as follows:
[0364] Butadiene was added to the second intermediate product and reacted at 100°C for 0.5h, then 3-amino-1-propylene was added and reacted in an alkaline environment at 110°C for 6h to obtain a polymer. The reaction schematic diagram is shown in the figure below, where R 1 , R 3 As in Example 1, s is 3, t is 3, the structural unit derived from butadiene and the structural unit derived from 3-amino-1-propylene are random copolymers,
[0365]
[0366] Example 5
[0367] The preparation method is similar to that of Example 1, except that the type of dispersant is changed. The first two steps of the dispersant synthesis process are consistent with those of Example 1. The preparation process of the polymer is as follows:
[0368] Butadiene was added to the second intermediate product and reacted at 100°C for 6.5 hours in an alkaline environment to obtain a polymer. The reaction schematic diagram is shown in the figure below, where R 1 , R 3 Same as in Example 1, s+t is 6,
[0369]
[0370] Example 6
[0371] The preparation method is similar to that of Example 1, except that the dispersant is different. The preparation method of the dispersant is to further react the product of Example 1 with 3-amino-1-propylene to prepare a polymer having an amino terminal group, the structure of which is shown below, wherein R 1 , R 3 , R 6 , n is consistent with that in Example 1,
[0372]
[0373] Example 7
[0374] The preparation method is similar to that of Example 1, except that the product of Example 1 is further reacted with acrylamide to prepare a polymer having an amide terminal group, the structure of which is shown below, wherein R 1 , R 3 , R 6 , n remain the same as in Example 1.
[0375]
[0376] The preparation method of Examples 8-15 is similar to that of Example 7, except that in Examples 8-11, the weight average molecular weight of the polymer is regulated by adjusting the degree of polymerization of the polyether segment, and in Examples 12-15, the amount of dispersant added is adjusted to keep the total mass of the positive electrode film layer unchanged. As the mass content of the dispersant changes, the mass percentage of the positive electrode active material is adjusted accordingly. For specific parameters, see Table 1.
[0377] The preparation method of Example 16 is similar to that of Example 3. In the preparation process of the dispersant, the organic monomer containing an unsaturated bond added during the preparation of the polymer is The structural formula of the dispersant prepared with m=4 is as follows:
[0378] Wherein R1, R3, s and t are consistent with those in Example 3.
[0379] Embodiment 17
[0380] The preparation method of Example 17 is basically the same as that of Example 7, except that the monomers added during the preparation of R1 are all ethylene oxide, so the polyether segment is polyethylene oxide.
[0381] Embodiment 18
[0382] The preparation method of Example 18 is basically the same as that of Example 7, except that the anchoring group of the dispersant in Example 7 is a phosphite group, and the preparation method is basically the same as that of the dispersant in Example 7, except that POCl is not initially added during the preparation process. 3 , but PCl 3 , its dispersant structure is shown below, where R 1 , R 3 , R 6 , n remain the same as in Example 1.
[0383]
[0384] Embodiment 19
[0385] The preparation method of Example 19 is basically the same as that of Example 7, except that R 3 Group and R 1 The groups are the same and are all polyether segments, wherein n2 is 12 and m2 is 13.
[0386] The preparation process of the dispersant is basically the same as that of Example 7, except that the preparation process of the second intermediate product is different, as follows:
[0387] Weigh 1,2-propylene glycol (ethylene oxide, propylene oxide monomer, POCl 3 The reactor was vacuumed and replaced with high-purity nitrogen three times. Ethylene oxide and propylene oxide were added in turn, with a molar ratio of n 2 :m 2 , block polymerization reaction was carried out, the pressure during the reaction was maintained at 0.3±0.05MPa, the temperature was maintained at 115±5℃, and POCl was added after 5h of reaction. 3 , dichloromethane (DCM) and sodium hydroxide, react at 115±5°C for 5 hours under nitrogen atmosphere, then add water and react at 50°C for 10 hours to generate the product. The reaction process diagram is shown below, where A 1 for n2 is 12 and m2 is 13.
[0388]
[0389] The product was further reacted in the same manner as in Example 7 to join R 2 group to generate phosphorus-containing polymers that act as dispersants.
[0390] Embodiment 20
[0391] The preparation method of Example 20 is basically the same as that of Example 7, except that the weight average molecular weight of the binder PVDF is 300,000; the ratio of the positive electrode active material carbon-coated lithium iron phosphate (LFP@C), the conductive agent carbon black (SP), the binder polyvinylidene fluoride (PVDF), and the dispersant is 96:2:1.5:0.5.
[0392] Embodiment 21
[0393] In Example 21, the Directly acts as a dispersant, no longer combined with R 2 Group.
[0394] Embodiment 22
[0395] The preparation method of Example 22 is basically the same as that of Example 19, except that the initial input in the synthesis process of the dispersant polyether segment is not 1,2-propylene glycol, but phenol, and the catalyst is potassium hydroxide, wherein A 1 for n2 is 12, m2 is 13, R 6 For -(CH 2 ) 4 -, n is 2.
[0396] Specifically, the dispersant is:
[0397]
[0398] Embodiment 23
[0399] In Example 23, the product prepared in the synthesis process of Example 22 is directly used as a dispersant, and the specific structural formula is as follows:
[0400]
[0401] Embodiment 24
[0402] The preparation methods of Example 24 and Example 23 are basically the same, except that in the last step of the preparation process of the product, water is not added for hydrolysis, but phenol is added to react at 50°C for 10 hours to generate the product, which is directly used as a dispersant. The specific structural formula is
[0403]
[0404] Embodiment 25
[0405] The preparation method of Example 25 is basically the same as that of Example 7, except that phenol is not initially added into the polyether segment synthesis process, and the product A 1 It is phenyl.
[0406] Embodiment 26
[0407] The preparation method of Example 26 is basically the same as that of Example 22, except that the positive electrode active material is carbon-coated lithium manganese iron phosphate, and the specific preparation method thereof is:
[0408] Step S1: 689.6g manganese carbonate, 455.27g ferrous carbonate, 4.65g cobalt sulfate, and 4.87g vanadium dichloride are added to a mixer and mixed thoroughly for 6h. The obtained mixture is then transferred to a reactor, and 5L deionized water and 1260.6g oxalic acid dihydrate are added, heated to 80°C, and stirred at a speed of 500rpm for 6h, mixed evenly, until the reaction is terminated and no bubbles are generated, to obtain a Fe, Co, and V co-doped manganese oxalate suspension. The suspension is then filtered, dried at 120°C, and sand-milled to obtain Fe, Co, V, and S co-doped manganese oxalate particles with a particle size of 100nm.
[0409] Step S2: Take 1793.1g of manganese oxalate prepared in step S1, 368.3g of lithium carbonate, 1146.6g of ammonium dihydrogen phosphate and 4.9g of dilute sulfuric acid, add them to 20L of deionized water, stir them thoroughly, and evenly mix and react at 80°C for 10h to obtain a slurry. The slurry is transferred to a spray drying device for spray drying and granulation to obtain a powder. In a protective atmosphere (90% nitrogen and 10% hydrogen), the powder is sintered in a roller kiln at 700°C for 4h to obtain the core of the positive electrode active material Li0.997Mn0.60Fe0.393V0.004Co0.003P0.997S0.003O4.
[0410] Step S3: PEG-3000 is selected as the first carbon source, 58.2g of PEG-1000 is dissolved in 500g of deionized water, and then stirred and fully dissolved to obtain an aqueous solution. 1571.9g of the above core material is added to the solution, and stirred and mixed for 6h until the mixture is uniformly mixed. After spray drying, a first sintering treatment is performed, and the first sintering treatment temperature is 600°C, and the first sintering treatment time is 9h, thereby obtaining a first coated positive electrode active material after the first sintering treatment;
[0411] Step S4: Glucose is selected as the second carbon source, 37.3 g of glucose is dissolved in 500 g of deionized water, and then stirred and fully dissolved to obtain a glucose aqueous solution. 1603.3 g of the first coated positive electrode active material obtained in step S3 is added to the aforementioned glucose solution, stirred and mixed for 6 hours until the mixture is uniformly mixed, and then spray-dried and subjected to a second sintering treatment, the temperature of the second sintering treatment is 750° C., and the time of the second sintering treatment is 20 hours, thereby obtaining a positive electrode active material after the second sintering treatment.
[0412] Examples 27-28
[0413] The preparation methods of Examples 27 and 28 are basically the same as those of Example 26, except that the preparation methods of the positive electrode active materials are different. The specific parameters of the differences are:
[0414] In Example 27, the first carbon source is PEG-10000, the first sintering temperature is 500°C, and the first sintering treatment time is 5 hours. The second carbon source is glucose, the second sintering temperature is 550°C, and the second sintering treatment time is 20 hours.
[0415] In Example 28, the first carbon source is PEG-2000, the first sintering temperature is 660° C., and the first sintering treatment time is 9 h. The second carbon source is sucrose, the second sintering temperature is 750° C., and the second sintering treatment time is 6 h.
[0416] Comparative Example
[0417] Comparative Example 1
[0418] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that no dispersant is added.
[0419] The preparation method of Comparative Example 2 is substantially the same as that of Example 1, except that the dispersant is
[0420]
[0421] Where a is 3 and b is 3.
[0422] Comparative Example 3
[0423] The preparation methods of Comparative Example 3 and Example 26 are basically the same, except that the dispersant in Comparative Example 3 is the same as that in Comparative Example 2.
[0424] Comparative Example 4
[0425] The preparation methods of Comparative Example 4 and Example 27 are basically the same, except that the dispersant in Comparative Example 4 is the same as that in Comparative Example 2.
[0426] Comparative Example 5
[0427] The preparation methods of Comparative Example 5 and Example 28 are basically the same, except that the dispersant in Comparative Example 5 is the same as that in Comparative Example 2.
[0428] 2. Performance Test
[0429] 1. Characterization of polymers
[0430] 1) Weight average molecular weight
[0431] A Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141) was used. A polystyrene solution sample with a mass fraction of 3.0% was used as a reference, and a matching chromatographic column was selected (oily: Styragel HT5 DMF7.8*300mm+Styragel HT4). A 3.0% polymer solution was prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution was allowed to stand for one day for use. During the test, tetrahydrofuran was first drawn with a syringe and rinsed, and repeated several times. Then 5 ml of the experimental solution was drawn, the air in the syringe was expelled, and the needle tip was wiped dry. Finally, the sample solution was slowly injected into the injection port. Data was obtained after the indication stabilized.
[0432] 2. Positive electrode active material
[0433] 1) Determination of hybrid morphology of carbon atoms in carbon coating layer:
[0434] Determination of hybrid morphology of carbon atoms in the carbon coating layer: This test is performed by Raman spectroscopy. By peak separation of the energy spectrum of the Raman test, I g / I d , where I d For sp 3 Peak intensity of carbon form, I g For sp 2 The peak intensity of the carbon morphology can be measured to confirm the molar ratio of the two.
[0435] 2) Carbon coating thickness test
[0436] The thickness of the carbon coating layer was tested by cutting a thin slice of about 100 nm from the middle of a single particle of the positive active material prepared above by FIB, and then performing a TEM test on the thin slice to obtain the original TEM test image and save the original image format (xx.dm3). The original image obtained by the above TEM test was opened in the Digital Micrograph software, and the carbon coating layer was identified through the lattice spacing and angle information, and the thickness of the carbon coating layer was measured. The thickness of the selected particle was measured at three positions and the average value was taken.
[0437] 3. Cathode slurry
[0438] 1) Maximum solid content of slurry
[0439] The maximum solid content of the positive electrode slurry refers to the maximum solid content of the slurry that meets the shipping viscosity between 4000 and 35000 mPa.s and does not gel after the slurry is left to stand for 24 hours. Slurry solid content test method: Take the slurry weight and record it as m 0 , placed in a weight loss tester; the slurry is evaporated until the weight loss rate is less than 0.3%, and the remaining weight is recorded as m 1; Solid content = m 1 / m 0 *100%
[0440] 2) Filtering time
[0441] Take an area of 30×30cm 2 Fold the 200-mesh filter into a funnel shape; take two beakers, place one on the table, and fill the other with 500 ml of slurry and pour it into the filter funnel, and record the filtration time of 300 ml of dripping slurry.
[0442] 4. Positive electrode
[0443] 1) Pole brittleness test
[0444] Take a defect-free sample with a compaction density of 2.6 g / cm 3 The positive electrode sheet is cut into samples with a length and width of 25cm*4cm along the longitudinal direction. The number of samples is ≥4. After pre-folding it in the longitudinal direction (25cm direction), the film is placed on the test platform and rolled once with a 2kg cylindrical roller. If it is light-transmitting, the number of times of brittle light transmission is 1. If it is not light-transmitting, repeat the reverse folding and rolling. Observe the crease against the light to see if it is light-transmitting or broken, record the actual number of folds, and take the average as the test result.
[0445] 5. Secondary battery
[0446] 1) Maximum volume energy density
[0447] The maximum volume energy density refers to the volume energy density of the battery measured when the positive electrode is at the ultimate compaction density. The smaller of the compaction density corresponding to the elongation of the electrode is 6‰ or the number of flexible folds of the electrode is 2 is defined as the ultimate compaction density.
[0448] The discharge energy measurement method of a battery cell is as follows:
[0449] The battery cell was left at rest at 25℃ for 2h to ensure that the temperature of the battery cell was 25℃. After charging the battery cell at 0.33C to the charge cut-off voltage at 25℃, the constant voltage charging was continued at the charge cut-off voltage until the current reached 0.05C and the charge was cut off (where C represents the rated capacity of the battery cell). After the battery cell was left at rest at 25℃ for 1h, the battery cell was discharged at 0.33C to the discharge cut-off voltage at 25℃, and the total discharge capacity C0 released by the battery cell was recorded, and the total discharge energy was E0.
[0450] The battery cell volume measurement method is as follows:
[0451] The length, width and height of the battery cell are measured to calculate the volume value M0 of the battery cell.
[0452] The formula for calculating battery energy density is as follows:
[0453] Battery energy density = battery cell discharge energy E0 / battery cell volume M0.
[0454] 2) Cycle capacity retention rate after 40 cycles at 25°C
[0455] The voltage calibration method is as follows:
[0456] Let the battery cell stand at 25℃ for 2h, ensuring the temperature of the battery cell is 25℃. Charge the battery cell to 4.25V at 0.33C0 at 25℃, charge at 4.25V constant voltage to a current of 0.05C0, and let stand for 1h. Discharge 0.95C0 at 0.33C0 at 25℃, and record the voltage V1 at this time. After standing for 5min, discharge at 0.33C0 at 25℃ to 2.0V. After standing for 5min, charge the battery cell to 0.97C0 at 0.33C0 at 25℃, and record the voltage V2 at this time.
[0457] The cycle test process is as follows:
[0458] Place the battery cell at 25°C for 2 hours to ensure that the temperature of the battery cell is 25°C. Charge the battery cell at 0.33C0 at 25°C to a voltage of V2 and place it at rest for 0.5 hours. Discharge the battery cell at 0.33C0 at 25°C to a voltage of V1 and record the capacity at this time as Cn. After placing it at rest for 0.5 hours, repeat the above steps until the number of cycles n is 40cls.
[0459] After cycling for 40 cls according to the above steps, Cn / C0 is recorded as the cycle capacity retention rate, which is used as an indicator to evaluate the battery cycle performance.
[0460] 3) Full battery cycle test:
[0461] At a constant temperature of 45°C, charge the full battery at 2.5V-4.3V at 1C to 4.3V, then charge at 4.3V at a constant voltage until the current is less than or equal to 0.05mA. Let it stand for 5 minutes, then discharge at 1C to 2.5V, and record the discharge capacity at this time as D 0 Repeat the above charge and discharge cycle until the discharge capacity drops to D 0 Record the number of cycles the battery has gone through.
[0462] III. Analysis of test results of various embodiments and comparative examples
[0463] Table 1
[0464]
[0465] From the comparison between the embodiments and the comparative examples, it can be seen that the embodiments all include the polymer dispersant shown in Formula I, which can effectively increase the maximum solid content of the slurry, shorten the filtration time, improve the production efficiency and quality of the electrode, and improve the flexibility of the electrode.
[0466] From the comparison between Examples 1-4 and Example 5, it can be seen that R 2 The organic chain segment contains at least one of an amide group and an amino group, which can further increase the maximum solid content of the slurry.
[0467] From the comparison between Examples 6-7 and Example 1, it can be seen that R 2 The terminal groups contain -C(O)-NH 2 、-CH 2 -NH 2 Compared with other end groups, at least one of the end groups can more effectively play the dispersing role of the polymer and increase the maximum solid content of the slurry.
[0468] From the comparison between Example 7 and Example 17, it can be seen that R 1 , R 3 At least one of them contains a poly(ethylene oxide-propylene oxide) polyether segment, which can more effectively play a dispersing and softening role than a polyethylene oxide polyether segment, and further improve the maximum solid content of the slurry and the flexibility of the electrode.
[0469] From the comparison between Example 19 and Example 7, it can be seen that when both R1 and R3 are polyether segments, the slurry filtration time can be further reduced and the electrode flexibility can be improved compared with only one of the two being a polyether segment.
[0470] From the comparison of Examples 7-11, it can be seen that the weight average molecular weight of the polymer is 2000-5000, which can further exert the dispersing effect, increase the maximum solid content of the slurry, and shorten the filtration time.
[0471] Table 2
[0472]
[0473] From the comparison between Example 22 and Example 19, the comparison between Example 25 and Example 7, and the comparison between Example 23 and Example 21, it can be seen that the end group of the polyether segment includes a phenyl group, which can further improve the dispersibility of the slurry.
[0474] Table 3
[0475]
[0476] As can be seen from Examples 12-15, based on the total mass of the dry material of the positive electrode slurry, the mass content of the polymer is 0.1%-2.0%, and the slurry has a high maximum solid content, a short filtration time, and high flexibility. When the mass content of the polymer is 0.2%-1.0% based on the total mass of the dry material of the positive electrode slurry, the processing performance of the pole piece and the energy density of the battery can be further taken into account.
[0477] Table 4
[0478]
[0479] From the comparison between Example 7 and Example 20, it can be seen that the positive electrode slurry includes a vinylidene fluoride polymer with a weight average molecular weight of not less than 700,000 as a binder, which can further reduce the amount of binder used and improve the flexibility of the electrode.
[0480] Table 5
[0481]
[0482] From the comparison between Example 7 and Example 18, it can be seen that phosphate polymers can more effectively increase the solid content of the slurry, shorten the filtration time, and improve the flexibility of the electrode compared to phosphite polymers; and phosphate polymers have better stability, and can effectively improve the cycle capacity retention rate of the battery on the basis of improving the dispersibility of the slurry.
[0483] Table 6
[0484]
[0485] From the comparison between Examples 26-28 and Comparative Examples 3-5, it can be seen that the polymers provided in the embodiments of the present application can more effectively improve the dispersibility of the positive electrode active material with a high degree of order in the carbon coating layer, and the processability, cycle stability and gram capacity of the battery can be simultaneously improved by matching the dispersant with the surface coating layer of the positive electrode active material.
[0486] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and the same effect as the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A polymer, characterized in that The polymer comprises a structure shown in Formula I, Wherein X comprises a phosphate group or a phosphite group, R1 and R3 each independently comprise at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 comprises a polyether segment or a polyester segment; and R2 comprises an organic segment.
2. The polymer according to claim 1, characterized in that The organic segment of R2 contains at least one of an amide group, an amino group, and an aromatic group.
3. The polymer according to claim 1 or 2, characterized in that The organic chain segment of R2 also includes C 2-12 Hydrocarbon.
4. The polymer according to any one of claims 1 to 3, characterized in that R2 comprises the structure shown in Formula II Among them, R4 and R5 are randomly copolymerized, and R4 includes C 2-12 Alkylidene, C 3-13 At least one of the amide groups, R5 includes At least one of; Wherein, q1, q2, q3, q4 each independently include any integer between 0 and 4, R6 a 、R6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
5. The polymer according to any one of claims 1 to 4, characterized in that R2 comprises the structure shown in Formula III Among them, R6 includes C 2-12 Alkylene, R7 includes At least one of; wherein, q5 and q6 each independently include any integer between 0-4, 1≤n≤6.
6. The polymer according to any one of claims 1 to 5, characterized in that The terminal group of R2 includes at least one of -C(O)-NH2 and -CH2-NH2.
7. The polymer according to any one of claims 1 to 6, characterized in that At least one of R1 and R3 comprises a polyether segment, and optionally, both R1 and R3 comprise a polyether segment.
8. The polymer according to any one of claims 1 to 7, characterized in that At least one of R1 and R3 comprises a polyether segment represented by formula IV Wherein EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50.
9. The polymer according to any one of claims 1 to 8, characterized in that The terminal groups of the polyether segments include aromatic groups.
10. The polymer according to any one of claims 1 to 9, characterized in that X includes a phosphate group.
11. The polymer according to any one of claims 1 to 10, characterized in that The polymer includes at least one of the polymers represented by the following formula: Wherein, at least one of R1 and R3 comprises a block copolymer polyether segment represented by formula IV wherein EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50, R6 and R4 each independently include C 4-8 Alkylene, C 4-8 At least one of alkenylene groups.
12. The polymer according to claim 11, characterized in that The terminal groups of the polyether segments include aromatic groups.
13. The polymer according to any one of claims 1 to 10, characterized in that The polymer is shown in the following formula: Wherein, R2 comprises at least one of hydrogen, aryl, substituted or unsubstituted alkyl, and an organic segment containing an amino group or an amide group, At least one of R1 and R3 comprises a block copolymer polyether segment represented by formula IV Wherein EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, 4≤m1≤50, 4≤n1≤50, and the terminal group of the polyether segment includes phenyl.
14. The polymer according to any one of claims 1 to 13, characterized in that The weight average molecular weight of the polymer is 1000-10000, and can be optionally 2000-5000.
15. A method for preparing a polymer, characterized in that: The preparation method comprises: The compound represented by formula VI is reacted with R3OH, R1OH, water, and a polymerizable monomer containing an unsaturated bond to prepare a polymer having a structure represented by formula I. Wherein, X includes a phosphate group or a phosphite group, X1, X2, and X3 all contain halogen; R1 and R3 each independently contain at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 contains a polyether segment or a polyester segment; and R2 includes an organic segment.
16. The preparation method according to claim 15, characterized in that: The preparation method comprises the following steps: The compound represented by formula VI is reacted with R3OH, R1OH and water to prepare the intermediate product represented by formula VII. The intermediate product is subjected to a second reaction with a polymerization monomer containing at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond to prepare the polymer.
17. The preparation method according to claim 16, characterized in that: The second reaction specifically comprises the following steps: The intermediate product undergoes an addition reaction with at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, and then undergoes a substitution reaction with a halogen-substituted organic alcohol; The polymer is prepared by cycling the addition reaction and substitution reaction in sequence for multiple times; Wherein, R2 comprises the structure shown in formula III Among them, R6 includes C 2-12 Hydrocarbyl, R7 includes At least one of; wherein, q5 and q6 each independently include any integer between 0-4, 1≤n≤6.
18. The preparation method according to claim 16, characterized in that: The preparation method further comprises the following steps: The intermediate product is subjected to a third reaction with (i) at least one of an amide containing an unsaturated bond and an amine containing an unsaturated bond, and (ii) at least one of a hydrocarbon monomer containing an unsaturated bond and a cyclic amide monomer to prepare the polymer, wherein R2 comprises a structure shown in Formula II: Among them, R4 and R5 are randomly copolymerized, and R4 includes C 2-12 Hydrocarbon, C 3-13 At least one of the amide groups, R5 includes At least one of; Wherein, q1, q2, q3, q4 each independently include any integer between 0 and 4, R6 a 、R6 b Contains hydrogen, C 1-4 At least one of the alkyl groups, 1≤s≤6, 1≤t≤10.
19. A method for preparing a polymer, characterized in that: The preparation method comprises: The compound represented by formula VI is reacted with raw materials including R3OH and R1OH to prepare a polymer having a structure represented by formula I, Wherein, X includes a phosphate group or a phosphite group, X1, X2, and X3 all include halogen; R1 and R3 each independently include at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 includes a polyether segment, and the end group of at least one of the polyether segments includes an aromatic group; R2 includes an organic segment.
20. Use of the polymer according to any one of claims 1 to 14 or the polymer prepared by the preparation method according to any one of claims 15 to 19 as a dispersant.
21. A positive electrode slurry, characterized in that: The invention comprises a dispersant, wherein the dispersant comprises the polymer according to any one of claims 1 to 14 or the polymer prepared by the preparation method according to any one of claims 15 to 19.
22. The positive electrode slurry according to claim 21, characterized in that The positive electrode slurry includes a positive electrode active material, and the positive electrode active material includes at least one of lithium phosphate and its carbon-modified materials; optionally, the positive electrode active material includes at least one of lithium iron phosphate and its doped materials, lithium iron manganese phosphate and its doped materials, carbon-coated materials of lithium iron phosphate and its doped materials, and carbon-coated materials of lithium iron manganese phosphate and its doped materials.
23. The positive electrode slurry according to claim 21 or 22, characterized in that: The positive electrode active material comprises a core and a carbon coating layer, wherein the carbon coating layer covers at least a portion of the surface of the core, wherein the carbon coating layer has a sp 2 Hybridized carbon atoms with sp 3 The molar ratio of hybridized carbon atoms is not less than 0.2, and may be not less than 0.5, and may be not less than 0.
8.
24. The positive electrode slurry according to claim 23, characterized in that: The thickness of the carbon coating layer is not greater than 15 nm; optionally, the thickness of the carbon coating layer is not greater than 10 nm; optionally, the thickness of the carbon coating layer is 4 nm-8 nm.
25. The positive electrode slurry according to any one of claims 21 to 24, characterized in that: Based on the total mass of dry materials in the positive electrode slurry, the mass content of the polymer is 0.1%-2.0%, and can be optionally 0.2%-1.0%.
26. The positive electrode slurry according to any one of claims 21 to 25, characterized in that: The positive electrode slurry includes a binder, and the binder includes a vinylidene fluoride polymer with a weight average molecular weight of not less than 300,000. Optionally, the weight average molecular weight of the binder is 700,000-9,000,000.
27. The positive electrode slurry according to any one of claims 21 to 26, characterized in that: The maximum solid content of the positive electrode slurry is not less than 60%, and can be selected from 60% to 80%.
28. A positive electrode plate, characterized in that: The positive electrode plate includes a positive electrode film layer, which is prepared by the positive electrode slurry described in any one of claims 21 to 27 or the positive electrode film layer includes a dispersant, and the dispersant includes a polymer described in any one of claims 1 to 14 or a polymer prepared by the preparation method described in any one of claims 15 to 19.
29. The positive electrode sheet according to claim 28, characterized in that: The positive electrode sheet has a compaction density of 2.6 g / cm 3 The number of folding times is not less than 2 times, and can be selected as 3-6 times.
30. The positive electrode sheet according to claim 28 or 29, characterized in that: The surface density of the positive electrode sheet is not less than 300 mg / 1540.25 cm 2 , optional: 300mg / 1540.25cm 2 -600 mg / 1540.25 cm 2 .
31. The positive electrode sheet according to any one of claims 28 to 30, characterized in that: The positive electrode film layer includes a dispersant, and the dispersant includes a structure shown in Formula I, wherein X comprises a phosphate group or a phosphite group, R1 and R3 each independently comprise at least one of a polyether segment, a polyester segment, hydrogen, and a hydrocarbon group, and at least one of R1 and R3 comprises a polyether segment or a polyester segment, and R2 comprises an organic segment; optionally, the organic segment of R2 comprises at least one of an amide group and an amino group, and optionally, the end group of the polyether segment comprises an aromatic group; The positive electrode active material includes at least one of lithium iron phosphate and its doping materials, lithium iron manganese phosphate and its doping materials, lithium iron phosphate and its doping materials, carbon-coated materials of lithium iron phosphate and its doping materials, and carbon-coated materials of lithium iron manganese phosphate and its doping materials; optionally, the positive electrode active material includes at least one of lithium iron manganese phosphate and its doping materials, and carbon-coated materials of lithium iron manganese phosphate and its doping materials; Based on the total mass of the positive electrode film layer, the mass content of the dispersant is 0.1%-2.0%, and can be optionally 0.2%-1.0%.
32. A secondary battery, characterized in that: A positive electrode sheet comprising any one of claims 28 to 31.
33. An electrical device, characterized in that: Includes the secondary battery as described in claim 32.
Citation Information
Patent Citations
Polymer electrolyte and preparation method therefor
CN110402516A
Polymer electrolyte and method for producing same
CN111819725A
Flame-retardant plasticizer and flame-retardant polymer-based composite material
CN113372550A
Polyoxyalkylene phosphonates and improved process for their synthesis
US20050227877A1
Positive electrode slurry, positive electrode plate and secondary battery comprising the positive electrode plate
US20230231137A1
Cited By
Polyether modified phosphate dispersing agent and application thereof
CN120149413A
Polyether-modified phosphate ester dispersant and use thereof
CN120149413B
Polymer and preparation method therefor, positive electrode sheet, secondary battery, and electric device
EP4741441A1